MULTIPLE SETTING UNTUK PENGATURAN BANDWIDTH MENGGUNAKAN SQUID PROXY SERVER - Gunawan, Yan; Sevani, Nina (Teknik dan Ilmu Komputer, 2012)
Unappropriate in bandwidth scheduling making some effect with internet cafÃÂ©Ã¢â¬â¢s performance. Lack of bandwidth can slowndown response time for internet. This condition absolutely contradict with user needs. Squid proxy server is one of solutions to keep internet access stability. We can configure proxy server to scheduling bandwidth depend with clientÃ¢â¬â¢s rush hour, blocking harmful website, and accelerate access from client to frequently visited website. The experiment result show significant difference access time to a website from client that using proxy server and client without using proxy server. The experiment also shows that with scheduling bandwidth, client of intenet cafÃÂ© get bandwidth correspond with their needs.ÃÂ ÃÂ Keywords: ÃÂ scheduling, bandwidth, squid proxy server, blocking, access time, website.